Designing Joyful Learning Experiences for Strengthening Learning Independence in Elementary IPAS Education - Sari, Wanda Puspita; Solihin, Muhammad; Fitri, Fitria Carli Wiseza (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Learning independence is an essential competency in elementary education, particularly in IPAS learning, which requires students to actively engage in observation, inquiry, discussion, and problem-solving activities. However, many elementary students still demonstrate limited initiative, responsibility, and self-regulation during the learning process. This study aimed to examine how the design and implementation of joyful learning experiences could strengthen students’ learning independence in elementary IPAS education. The study employed a Classroom Action Research design based on the Kemmis and McTaggart model, consisting of two action cycles. The research was conducted with 14 fourth-grade students at Madrasah Ibtidaiyah Negeri 4 Bungo during the 2025/2026 academic year. Joyful learning experiences were designed through educational games, collaborative discussions, contextual exploration activities, presentations, and reflective learning tasks. Data were collected through observation and documentation and analyzed using descriptive quantitative and qualitative techniques. Learning independence was assessed through four dimensions: self-confidence, learning discipline, responsibility, and learning initiative. The findings revealed continuous improvement across all dimensions throughout the intervention cycles. The average level of learning independence increased from 43% in the pre-cycle phase to 59.5% in Cycle I and reached 79.5% in Cycle II. The greatest improvement was observed in learning initiative, while responsibility consistently achieved the highest scores. These findings indicate that joyful learning experiences can create meaningful and student-centered learning environments that support the development of learning independence and self-regulated learning in elementary IPAS education.